Mystery and Detective Fiction in the Victorian Period: Origins, Development, and Significance of Detective Fiction in English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the present scenario where, English Literature stands as a pivotal area of research and development, off-beat genres have taken a step ahead as areas of interest among scholars. Detective fiction which came into the literary scene in the second half of the Victorian Age, found its first prominent clues in the novels of Wilkie Collins. Though the chronology of detective fiction is short, it bloomed in the early years of the twentieth century through the works of great writers such as Sir Arthur Conan Doyle who gave the world the most fascinating fictional detective figure i.e. Sherlock Holmes. The expanse of the genre, then, became inclusive of scientific understanding and techniques. As interdisciplinary swept in detective fiction, kaleidoscopic views and analysis were generated regarding the works of detection. The genre became more prominent with writers like Agatha Christie and later J.K Rowling, Joe Pickett, etc. Detective fiction continues to flourish as a genre in the twentieth first century and is also welcomed in the form of adaptations on the digital screen and television. The paper aims to highlight the origin of Detective fiction and the journey of its development to one of the most eminent genres in the present time. The paper briefly throws light on oeuvre of Wilkie Collins and Sir Arthur Conan Doyle who were the pioneers in the progress of the genre. The paper seeks to establish the significance and relevance of detective fiction and the various factors that led to its rise in the field of English Literature.